2020
DOI: 10.1042/bsr20193396
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides inhibit ovarian cancer cell growth via microRNA-27a/FBXW7 signaling pathway

Abstract: Astragalus polysaccharide (APS), a natural antioxidant found in Astragalus membranaceus emerging as a novel anticancer agent, exerts antiproliferative and pro-apoptotic activity in various cancer cell types, but its effect on ovarian cancer (OC) remains unknown. In the present study, we tried to elucidate the role and mechanism of APS in OC cells. Our results showed that APS treatment suppressed the proliferation and induced apoptosis in OC cells. Afterward, the microRNA (miRNA) profiles in APS-treated cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…FBXW7 expression is downregulated in OC tissues, and low FBXW7 expression is negatively associated with the malignant potential of OC (14). Increasing evidence has suggested that FBXW7-knockdown can promote OC cell invasion and migration (36). The results of the present study demonstrated that overexpression of FBXW7 inhibited the invasion, migration, EMT and angiogenesis of OC cells.…”
Section: Discussionsupporting
confidence: 54%
“…FBXW7 expression is downregulated in OC tissues, and low FBXW7 expression is negatively associated with the malignant potential of OC (14). Increasing evidence has suggested that FBXW7-knockdown can promote OC cell invasion and migration (36). The results of the present study demonstrated that overexpression of FBXW7 inhibited the invasion, migration, EMT and angiogenesis of OC cells.…”
Section: Discussionsupporting
confidence: 54%
“…In both cell lines, miR-27a upregulation obviously reversed the inhibitory effects exhibited by APS, such as antiproliferation and proapoptotic. It produced the same as the effects of knockdown of FBXW7 by si-FBXW7 [ 64 ]. Tanshinone IIA (Tan-IIA) is a natural plant-derived component enriched in Chinese herbal medicine DanShen.…”
Section: Mechanisms With Natural Plants Compound In Ovarian Cancer Cellsmentioning
confidence: 99%
“…Just as it was reported in the previous study by Mushtaq Ahmad et al, the SNP effects the size of the terminal loop in the precursor miRNA of miR-27a and then modify the common breast cancer risk, which was very common in female population [24]. And in ovarian cancer cell lines, another common female cancer cell line, the F-box and WD-40 domain protein 7 (FBXW7), a classical tumor suppressor, was found directly targeted by miR-27a and its translation was suppressed by miR-27a [25]. Furthermore, Zhang et al found that miR-27a promoted the progression of ovarian cancer cells and induced the process of EMT via the Wnt/β-catenin signalling pathway through inhibition of FOXO1 [26].…”
Section: Associations Of Haplotypes With Ptb Riskmentioning
confidence: 99%